When celebrations go wrong: a case series of injuries after celebrating in sports - Momaya, A.; Read, C.; Estes, R. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Athletes often engage in various celebration maneuvers during sports events. These celebrations can result in acute injuries. Our objective was to document publicized injuries in collegiate and professional athletes resulting from celebrations and examine associated variables.